Public images, private readings : multi-perspective approaches to the Post-Palaeolithic rock art : proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain).: multi-perspective approaches to the Post-Palaeolithic rock art : proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain). Volume 5, Session A11e (2016) - Unknown
No abstract available